An experimental study for the characterisation of gas/liquid flow splitting at T-junctions - Conte, Giuseppe (2000)
In two-phase gas/liquid flow, the phenomenon of maldistribution of the phases occurring downstream of a splitting T-junction has been the topic of investigation of several authors. The negative consequences of this maldistribution on the operation of downstream unit have often led to the conclusion that T-junctions in two-phase pipelines are to be avoided. However, the large degree of segregation of the phases obtained at the outlets of a T-junction for certain flow rates and geometries, has encouraged Industry and researchers to exploit this simple device as a partial phases separator.